CRAMBE’S HIDDEN WEAPON: 2S ALBUMIN’S POTENTIAL IN TARGETING TRYPANOSOMA CRUZI - Silva, Darcy Ribeiro; Luiz , Queiroz Fernandes Pires; Camila, Borges Barbosa (American Research Journal of Nursing and Health Sciences (ARJNHS), 2023)
Plant storage proteins play a vital role in the growth and maintenance of seedlings, and their significance extends beyond basic plant survival. In mature seeds, a substantial portion of proteins, ranging from 80% to 90%, consists of distinct groups of storage proteins. These proteins not only serve as a source of nutrition but also possess remarkable properties, including antinutritional, antimicrobial, and even anti-cancer activities. Among these multifaceted plant compounds, a subgroup known as plant antimicrobial peptides has garnered considerable attention. These peptides are classified into various families, such as thionins, defensins, and cyclotides. While the antinutritional properties of some storage proteins serve as a defense mechanism for plants, they also have significant implications for human health. Thionins derived from wheat isoforms and PTH1 defensin from potatoes have demonstrated leishmanicidal activities, showcasing their potential as therapeutic agents. Similarly, certain plant antimicrobial peptides, particularly α- and β-defensins and cathelicidin, have exhibited action against African Trypanosomes, including Trypanosoma brucei and subspecies. Intriguingly, the repertoire of plant-derived antimicrobial and leishmanicidal peptides is extensive, but there is a notable gap in our understanding of the potential leishmanicidal activity of 2S albumin, a class of small proteins with a conserved pattern of cysteines linked by disulfide bridges. This study aims to address this gap by investigating the impact of 2S albumins derived from crambe seeds on Trypanosoma cruzi, the protozoan responsible for Chagas disease. Typically, 2S albumins are characterized by their small size (12–15 kDa) and conserved cysteine pattern, making them increasingly intriguing subjects for clinical research.